HOW EASE OF USE, USEFULNESS TOWARD ATTITUDE OF SHOPPING AT ONLINE RETAIL - Ida Zuniarti; Dede Suleman; Susan Rachmawati; Sabil; Sri Rusiyati (Dinasti International Journal of Education Management And Social Science, 2020)
This study aims to analyze the relationship between ease of use and usefulness of shopping decisions at online retail. This study uses a sampling quota sampling technique with a survey method with a total sample of 90 respondents from the city of Jakarta with the criteria of respondents aged over 17 years and have made a purchase of fashion products online. The results of the study stated that ease of use and usefulness influence consumer attitudes. the results of this study can be a reference for further research.